TIME EVOLUTION OF THE GROWTH OF VERTICALLY ALIGNED CARBON NANOTUBES USING PALM OIL - Abu Bakar, Suriani (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2017)
We studied the change in morphology and microstructure of carbon nanotubes (CNT) grown for 5, 10, 15, 20, 25, 30, 35 and 40 mins respectively. The CNT was fabricated from palm oil using thermal chemical vapor deposition method at fixed synthesis temperature of 750Â°C in argon ambient. The samples were analyzed using field emission scanning electron microscopy and micro-Raman spectroscopy. At 5 min of growing time, a very thin layer of CNT was produced without any vertical growth of CNT. The tube walls were also defective and coated with amorphous carbon. The vertically aligned CNT (VACNT) was initially observed at 10 min synthesis time and the length increases with prolonged synthesis time at various growth rate. It should also be highlighted that as the nanotubes get longer and thickens with time, the development of secondary growth structures was also spotted particularly for synthesis time more than 30 min. From Energy-dispersive X-ray spectroscopy analysis, it is justifiable that the generation of secondary growth came from the raised catalyst. As a conclusion, it can be said that, the optimum synthesis time for higher growth rate VACNT, smaller diameter and mix with single-walled CNT, low ID/IG ratio was identified at 30 min time.Key words: Nanotubes, Chemical synthesis method, Scanning electron microscopy (SEM) and Raman spectra.ABSTRAKÂ Kami mengkaji perubahan morfologi dan struktur mikro tabung nano karbon (CNT) yang ditumbuhkan selama 5, 10, 15, 20, 25, 30, 35 dan 40 menit. CNT difabrikasi dari minyak sawit menggunakan metode deposisi uap kimia termal pada suhu sintesis 750 Â°C dalam lingkungan argon. Sampel dianalisis menggunakan mikroskop elektron dan spektroskopi mikro-Raman. Pada waktu pertumbuhan 5 menit, diperoleh lapisan CNT yang sangat tipis tanpa pertumbuhan vertikal CNT. Dinding tabung juga rusak dan dilapisi dengan karbon amorf. Pertumbuhan CNT vertikal sejajar (VACNT) pada awalnya teramati pada waktu sintesis 10 menit dan panjangnya bertambah seiring dengan perpanjangan waktu sintesis di berbagai tingkat pertumbuhan. Harus digarisbawahi pula bahwa semakin panjang dan tebal tabung nano seiring bertambahnya waktu, perkembangan struktur pertumbuhan sekunder juga terlihat terutama untuk waktu sintesis lebih dari 30 menit. Dari analisis spektroskopi energi dispersif sinar-X, terlihat bahwa generasi pertumbuhan sekunder berasal dari katalis yang terangkat. Sebagai kesimpulan, dapat dikatakan bahwa waktu sintesis optimal untuk tingkat pertumbuhan VACNT yang lebih tinggi, diameter lebih kecil, bercampur dengan CNT berdinding tunggal, dan rasio ID/IG rendah diidentifikasi pada 30 waktu menit.Kata Kunci: tabung nano karbon, metode sintesis kimiawi, mikroskop electron (SEM), spectrum Raman